Protection of Microgrid Feeders Using Impedance Angle Analysis Assisted by Synchrophasor Units - Sunil Kumar; Ikbal Ali; Anwar Siddiqui (Journal of Renewable Energy and Environment)
The healthy operation of a microgrid is a more challenging task due to the inclusion of various distribution generation (DG) sources. The incorporation of a grid with various distributed sources alters the radial structure of the network, making it challenging to manage this type of microgrid system, particularly in the event of a fault. A new protection scheme is designed to operate the microgrid and detect faults. This scheme is designed for detecting internal faults as well as external faults. The proposed scheme also determines the location of the fault. The proposed technique utilizes the cumulative sum of the differential positive-sequence impedance angle (DPSIA) as a constraint for fault detection, triggering the trip signal. The proposed scheme is based on the phasor measurement unit, which helps to calculate the positive sequence impedance angle. The setup, comprising 15 buses, is formulated using the real-time structured computer-aided design (RSCAD) platform in conjunction with the real-time digital simulator (RTDS). Phasor Measurement Units (PMUs) compliant with the IEEE C37.118.1 standard are strategically placed at key locations to accurately and reliably measure phasor quantities. This ensures the precise detection of faulted conditions with a high level of accuracy. The pre-fault and post-fault phasor components of voltage and current are assessed in proximity to the bus nearest to the fault location. The simulation results clearly indicate waveforms for internal and external faults at different locations of the feeder.